2004
DOI: 10.1158/0008-5472.can-04-1234
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Analysis Reveals Activation of Growth Promoting Signaling Pathways by Tenascin-C

Abstract: Tenascin-C is an adhesion-modulating extracellular matrix molecule that is highly expressed in tumor stroma and stimulates tumor cell proliferation. Adhesion of T98G glioblastoma cells to a fibronectin substratum is inhibited by tenascin-C. To address the mechanism of action, we performed a RNA expression analysis of T89G cells grown in the presence or absence of tenascin-C and found that tenascin-C down-regulates tropomyosin-1. Upon overexpression of tropomyosin-1, cell spreading on a fibronectin/tenascin-C s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 47 publications
(43 reference statements)
0
52
0
7
Order By: Relevance
“…The identification of tenascin-C as a facilitatory factor for glioma invasiveness in a three-dimensional matrix is relevant because it is increased in brain tumors where its expression increases with tumor grade (15,16,18,20,38). In vitro studies have found that tenascin-C increases the migration of glioma cells in monolayer or spheroid cultures (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of tenascin-C as a facilitatory factor for glioma invasiveness in a three-dimensional matrix is relevant because it is increased in brain tumors where its expression increases with tumor grade (15,16,18,20,38). In vitro studies have found that tenascin-C increases the migration of glioma cells in monolayer or spheroid cultures (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…In malignant gliomas, many ECM components are overexpressed both in the tumor stroma and at the advancing edge of the tumor within brain parenchyma. These ECM molecules include vitronectin, collagen I, collagen IV, osteopontin, tenascin-C, secreted protein acidic and rich in cysteine, and brain enriched hyaluronan binding (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Glioma invasion is thought to occur along ECM protein-containing structures, such as along tracts of myelinated fibers (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all known binding sites lie in the fibronectin type III repeats or the fibrinogen globe, but evidence has been reported suggesting that the EGF-like repeats act as low affinity ligands for EGF receptors (15). As a consequence, cell interactions with tenascin-C are quite complex, and several signaling mechanisms have been identified, including recent observations that tenascin-C blocks focal adhesion kinase-and Rho-mediated signaling pathways activated by fibronectin (2,16,17) as well as stimulating Wnt and other growth-promoting pathways (18). For a detailed discussion of these mechanisms, please refer to Gertrude Orend's recent review (4).…”
Section: About the Familymentioning
confidence: 99%
“…In mixed substrata of fibronectin and tenascin-C the antiadhesive effect is mediated by binding of tenascin-C to the HepII/syndecan-4 binding site in the FN3-13 repeat of fibronectin, thereby inhibiting the coreceptor function of syndecan-4 in fibronectin-mediated cell spreading (Huang et al 2001;Midwood et al 2004). In consequence, the activities of RhoA and focal adhesion kinase are compromised: cells redistribute their actin to the cell cortex and downregulate focal adhesion formation (Wenk et al 2000;Midwood and Schwarzbauer 2002;Ruiz et al 2004;Lange et al 2007). This might be a general mechanism for adhesion modulation, because fibulin-1 was also shown to modulate cell adhesion to fibronectin in this way (Williams and Schwarzbauer 2009).…”
Section: Tenascins In Cell Adhesion Modulationmentioning
confidence: 99%
“…Activation of many of the major signaling pathways can lead to induction of tenascin-C and/or tenascin-W expression (Table 2). In turn, plating cells on tenascin-C-containing substrata can affect several signaling pathways, such as induction of signaling through 14-3-3 tau Martin et al 2003) MAPK and Wnt (Ruiz et al 2004) or inhibition of the small GTPase RhoA known to induce actin stress fiber formation (Wenk et al 2000). Thus, some of the same pathways that initially trigger tenascin-C expression potentially lead to negative (in the case of RhoA) or positive (in the case of MAPK and Wnt signaling) feedback loops.…”
Section: Regulation Of Tenascin Expressionmentioning
confidence: 99%